Karakteristik Pengeringan Biji Pala (Myristica fragranshoutt) Menggunakan Alat Pengering Hybrid dengan Sumber Panas Dari energi Surya dan Serbuk Kayu - Debi Sarnadi; Raida Agustina; Rita Khathir (Jurnal Ilmiah Mahasiswa Pertanian, 2018)
Abstrak. Manfaat dari proses pengeringan pala yaitu untuk tujuan pengawetan. Tujuan penelitian ini adalah untuk mengkaji proses pengeringan biji pala menggunakan alat pengering hybrid dengan sumber energi matahari dan biomassa serbuk kayu. Total biji pala yang dikeringkan adalah 15 kg. Pembakaran serbuk kayu dilakukan selama pengeringan di malam hari dengan laju 3kg/jam. Parameter penelitian meliputi iradiasi surya, temperatur, kelembaban relatif, kadar air, dan uji organoleptik terhadap warna dan aroma. Hasil penelitian menunjukkan bahwa iradiasi rata-rata yang diperoleh adalah 131,61 W/m2 pada hari pertama dan dihari kedua 131,08  W/m2. Temperatur dalam ruang pengering (44°C) lebih tinggi dibandingkan dengan temperatur lingkungan (33,5°C). Kelembaban relatif rata-rata ruang pengering (27,7%) lebih rendah dari kelembaban relatif rata-rata di lingkungan (42,7%). Untuk mencapai kadar air biji pala 10% dibutuhkan waktu 32 jam secara kontinu dengan alat pengering  dan 39 jam selama 4 hari secara intermitten dengan metode penjemuran. Kapasitas alat pengering 2x lebih besar dari kapasitas penjemuran, dan biji pala kering menggunakan alat pengering lebih disukai oleh panelis dari segi warna dan aromanya.Drying Characteristics of Nutmeg Seed (Myristica Fragranshoutt) by Using a Hybrid Dryer Used Heat Sources from Solar and Sawdust EnergyAbstract. The benefit of drying process of nutmeg seed is to prolong its life. The objective of the study was to observe the drying method of nutmeg seed by using a hybrid dryer used the heat sources from solar and biomass (sawdust) energy. The total nutmeg seed used in this study was approximately 15 kg. The combustion rate of biomass during the night was 3kg/h. The parameters investigated were solar irradiation, temperature, relative humidity, moisture content and organoleptic test on color and flavor. The results showed that the average solar irradiation was 131.61 W/m2 on the first and second day drying. The average temperature in the drying chamber (44°C) was higher than the average ambient temperature (33.5°C). The average relative humidity in the drying chamber (27.7%) was lower than the average ambient relative humidity (42.7%). To have the final moisture of nutmeg seed 10%, the drying time needed was 32 hours continuously by using hybrid dryer and 39 hours for 4 days intermittent by sundrying method.The dryer capacity was double of sundrying capacity, and the color and flavor of dried nutmeg seed produced by using hybrid dryer was preferred by respondents.Abstract. The benefit of drying process of nutmeg seed is to prolong its life. The objective of the study was to observe the drying method of nutmeg seed by using a hybrid dryer used the heat sources from solar and biomass (sawdust) energy. The total nutmeg seed used in this study was approximately 15 kg. The combustion rate of biomass during the night was 3kg/h. The parameters investigated were solar irradiation, temperature, relative humidity, moisture content and organoleptic test on color and flavor. The results showed that the average solar irradiation was 131.61 W/m2 on the first and second day drying. The average temperature in the drying chamber (44°C) was higher than the average ambient temperature (33.5°C). The average relative humidity in the drying chamber (27.7%) was lower than the average ambient relative humidity (42.7%). To have the final moisture of nutmeg seed 10%, the drying time needed was 32 hours continuously by using hybrid dryer and 39 hours for 4 days intermittent by sundrying method. The dryer capacity was double of sundrying capacity, and the color and flavor of dried nutmeg seed produced by using hybrid dryer was preferred by respondents.